Striving: Feeling the sublime - Gadris, Stelios (Con-Textos Kantianos. International Journal of Philosophy, 2020)
In what follows, I will try to show how the sublime reveals a fundamental aspect of the subject as a human being: a striving to comprehend the absolute. Although at first this striving appears to lead to a futile pursuit – we cannot represent the absolute – we ultimately succeed in presenting it (as a symbol or in art), thus re-affirming the fundamental role of intuition for the human being: the need to make our notions, concepts and ideas tangible. The sublime thus appears to be in close relation to an aesthetic idea, symbols and art, manifesting a profound kinship between reason and the imagination.